Low ferroportin expression in AML is correlated with good risk cytogenetics, improved outcomes and increased sensitivity to chemotherapy. (May 2019) - Gasparetto, Maura; Pei, Shanshan; Minhajuddin, Mohammad; Stevens, Brett; Smith, Clayton A.; Seligman, Paul
Graphical abstract: Highlights: AMLs with low levels of ferroportin (FPN) have improved outcomes. Core Binding Factor AMLs have low levels of FPN compared to other AMLs. Lower levels of FPN lead to an increased sensitivity to chemotherapy. FPN may have prognostic significance and play a role in chemosensitivity. Abstract: Iron metabolism is altered in a variety of cancers; however, little is known about the role of iron metabolism in the biology and response to therapy of acute myeloid leukemia (AML). Here we show that SLC40A1, the gene encoding the iron exporter ferroportin (FPN), is variably expressed among primary AMLs and that low levels are associated with good prognosis and improved outcomes. In particular, core binding factor (CBF) AMLs, which are associated with good outcomes with chemotherapy, consistently have low level of SLC40A1 expression. AML cell lines that expressed relatively low levels of FPN endogenously, or were engineered via gene knockdown, had an increased sensitivity to chemotherapy relative to controls expressing high levels of FPN. Primary FPN low AML bulk cells also had increased sensitivity to Ara-C treatment, iron treatment and the combination of Ara-C and iron relative to FPN high cells. FPN low leukemic stem cells (LSCs) had decreased viability following addition of iron alone and in combination with Ara-C treatment relative to FPN high LSCs. Together these observations suggest a model where FPN mediated iron metabolism may play a role in chemosensitivity and outcome to therapy in AML.